Creative Firms as Change Agents in Creative Spaces - Kourtit, Karima; Nijkamp, Peter (Quaestiones Geographicae, 2012)
This paper focuses attention on a quantitative analysis of the creative sector. After a selective and concise literature review, it discusses three important methodological advances, viz. a spatial-econometric approach, a non-parametric business performance analysis based on Data Envelopment Analysis, and finally, a comprehensive and integrated modelling framework in which a so-called ‘Flying Disc’ model is used as a tool for specifying and estimating a Structural Equations Model. The paper offers finally some concluding remarks.